(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
One of the many topics which cause considerable difficulties for Mongolian students studying Russian is the Conditional Verbs and their translation. Therefore, in this article we will discuss the formation, function, and features of the use of Russian Conditional Verbs, as well as how to translate them into Mongolian. As example of how to translate is taken from the famous story “The Fate of Man” by the famous Russian – Soviet writer and Nobel Laureate Sholokhov M., translated by the leading Mongolian scholar and renowned translator of the XX century, one of the founders of our country’s modern literature, State Laureate Rinchin Byamba. The main result of this article: provide detailed information from master and doctoral level courses on Russian Conditional Verbs, discuss the different positions of scholars, report on the difficulties. Mongolian students face this topic, and present classic case studies translated into Mongolian. Орос хэлний нөхцөлт үйл (деепричастие), түүний утгыг монгол хэлэнд буулгах тухай асуудалд Хураангуй: Орос хэл үзэж буй монгол оюутан суралцагчдад нэлээд бэрхшээл учруулдаг олон сэдэв байдгийн нэг нь нөхцөлт үйл, түүний орчуулга юм. Иймд орос хэлний нөхцөлт үйл үгийн үүрэг, хэрэглээний онцлог хийгээд түүнийг монгол хэлэнд хэрхэн орчуулах талаар энэхүү өгүүлэлд товч багцлан харуулахыг зорив. Хэрхэн орчуулах тухай жишээ баримтыг нэрт эрдэмтэн, орчуулагч, Төрийн соёрхолт Бямбын Ринчиний орчуулсан орос-зөвлөлтийн нэрт зохиолч, Нобелийн шагналт М.Шолоховын “Хүний хувь заяа” өгүүллэгээс авсан болно. Орос хэлний нөхцөлт үйл үгийн тухайд магистрантур, докторантурын түвшний сургалтаас хальсан дэлгэрэнгүй мэдээлэл өгч, эрдэмтэн судлаачдын зөрүүтэй байр суурийн талаар өгүүлэн, энэ сэдвийг судлах явцад монгол суралцагчдад ямар бэрхшээл тулгардаг талаар мэдээлж, монгол хэлэнд орчуулсан сонгодог жишээ баримттай танилцуулсан нь энэхүү өгүүллийн гол үр дүн хэмээн үзэж байна. Түлхүүр үг: төгс ба төгс бус байдал, нийцэл болон дүйцлийн зарчим, үндэсний онцлог